2003
DOI: 10.1002/nbm.838
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of brain lactate in neuronal metabolism

Abstract: The involvement of brain lactate in neuronal metabolism was analyzed by ex vivo NMR spectroscopy with rats under the effects of pentobarbital, chloralose or morphine, which were infused with a solution of either [1-13 C]glucose þ lactate or glucose þ [3-13 C]lactate for 20 min. Electroencephalogram recordings indicated different brain electrical activity levels under the three drugs with a clear distinction between pentobarbital, on the one hand, and chloralose and morphine on the other. Labeling of metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
33
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 22 publications
9
33
1
1
Order By: Relevance
“…The sole potential pyruvate source was the lactate endogenous to brain, providing that the latter was synthesized in a compartment other than the neurons. As evidenced previously from acetylCoA enrichment analysis (17), the astrocytes were mainly responsible for the brain lactate production, a finding in agreement with the much more efficient lactate production by astrocytes than by neurons (15). Therefore, the amino acid labeling patterns could be due to a progressively more pronounced involvement of astrocytic glycolytic lactate than of blood lactate in the move from pentobarbital to morphine.…”
Section: Involvement Of Brain Lactate In the Neuronal Metabolism-supporting
confidence: 86%
See 3 more Smart Citations
“…The sole potential pyruvate source was the lactate endogenous to brain, providing that the latter was synthesized in a compartment other than the neurons. As evidenced previously from acetylCoA enrichment analysis (17), the astrocytes were mainly responsible for the brain lactate production, a finding in agreement with the much more efficient lactate production by astrocytes than by neurons (15). Therefore, the amino acid labeling patterns could be due to a progressively more pronounced involvement of astrocytic glycolytic lactate than of blood lactate in the move from pentobarbital to morphine.…”
Section: Involvement Of Brain Lactate In the Neuronal Metabolism-supporting
confidence: 86%
“…Physiological Status of the Infused Rats-As reported previously, an electroencephalogram recording indicated that the rat cerebral activity was strongly depressed under pentobarbital anesthesia, whereas a slight increase in spectral power in the 1-20 Hz frequency band was noted under both ␣-chloralose and morphine as a consequence of a large power increase in the ␦ band, whereas ␣-chloralose induced a slight power decrease in the band (17). At the end of infusion, PaO 2 was 74 Ϯ 5, 84 Ϯ 1, or 82 Ϯ 2 and PaCO 2 was 53 Ϯ 2, 51 Ϯ 1, or 40 Ϯ 1 under pentobarbital, ␣-chloralose, or morphine anesthesia, respectively.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Although this concept of lactate shuttle was proposed long ago, it received lot of resistance from the scientific community especially from those who believed that glucose is the sole substrate in the brain (30;31). However now, it is getting accepted that lactose is also used as a main substrate for energy production under normal conditions (32)(33)(34). The direction of lactate flow between various cell types in the brain as well as its relative contribution with respect to glucose to the overall energy production is still debatable and not yet fully understood.…”
Section: Pathways Related To Energy Metabolism In Bbb and Brain: Lactmentioning
confidence: 99%